Plankton, hydrography, tides, etc. Part C [electronic resource] : tidal investigations and results - Dawson, W. Bell (William Bell), 1854-1944.; Canadian Arctic Expedition (1913-1918) (Ottawa : T. Mulvey, 1920)
Tables. Original issued in series: Report of the Canadian Arctic Expedition, 1913-1918 v. 10, pt. C. Includes list of titles in the series. Electronic reproduction. Mode of access: Internet. 44